Kerja Sama Pemerintah Daerah Guna Menunjang Penguatan Peran dalam Tahap Prabencana - Ayusari, Antonia Claudia Patricia Elsiputri; Firdausy, Adriana Grahani (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
Strengthening the role of local government in the dimension of cooperation requires the support of external parties to support the implementation of its duties and functions. This research uses a sociolegal type with a qualitative nature and approach. The types of data and data sources used are divided into primary and secondary. The results showed that the obstacles felt by the region consisted of two, first the limited budget and its absorption that had not been earmarked for pre-disaster. In addition, public awareness to love and preserve the environment also affects the formation of preparedness. Cooperation with external parties to strengthen the role of local governments can be done to overcome these obstacles, both through non-governmental organizations and between other local governments in pre-disaster activities.